Performance evaluation of organizational units with the hybrid approach of intuitionistic fuzzy DEMATEL-ELECTRE - Maryam Daneshvar; Fatemeh Karimi Jafari; Zahra Moradi Golriz (تصمیم گیری و تحقیق در عملیات)
Purpose: The management and performance evaluation system as one of the management processes has a prominent role in helping to achieve the goals and missions of the organization. The purpose of this article is to present a method to evaluate the performance of the organization's task units. This approach, based on a scientific and systematic method, explicitly considers the existence of uncertainty and ambiguity in the nature of organizational activities.Methodology: In this paper, a MADM hybrid approach is used. First, the performance indicators have been determined by the literature review and consulting experts, and then the importance and weight of each of the performance indicators has been calculated using the intuitionistic Fuzzy DEMATEL and finally, the performance of organization's units has been evaluated using the ELECTRE intuitionistic Fuzzy method. In order to apply this method, the performance evaluation of the organization of industry, mining and trade of Tehran province has been done with the proposed method.Findings: This study shows the effectiveness of the hybrid intuitionistic fuzzy DEMATEL-ELECTRE approach in performance evaluation the organizational units. This method correctly considers the uncertainty in the performance evaluation indicators by using the intuitionistic fuzzy approach and leads to a correct and reliable performance evaluation. The results showed that among performance indicators, organizational improvement and transformation, transparency and productivity improvement have the most weight and importance in performance evaluation of organizational units.Originality/Value: For the first time, this research has used the hybrid intuitionistic fuzzy DEMATEL-ELECTRE approach to performance evaluation of organizational units. Using the intuitionistic fuzzy approach provides a unique perspective on uncertainty in performance evaluation and increases the reliability of performance evaluation and ranking. The application of this method in a government service organization provides a methodological tool for performance evaluation or rating of organizational units or work teams in different or similar organizations and fields.